STUDI KOMPARATIF ZOOM DAN GOOGLE MEET DALAM PEMBELAJARAN DARING: PREFERENSI DAN KETERLIBATAN MAHASISWA - Sinaga, Andromeda Valentino; Sianipar, Rimma (Jurnal Muria Research Guidance and Counseling (MRGC), 2025)
This study compares Zoom and Google Meet in online learning to examine students' preferences and engagement. The research was conducted at Universitas Negeri Makassar with respondents from 4th-semester students of the Educational Technology Study Program. The method used was an experiment, where students attended classes using both platforms and then completed a survey. The results showed that 65% of students were more active when using Zoom, while 35% felt more comfortable with Google Meet. In terms of convenience, 60% preferred Zoom, and 40% preferred Google Meet. Zoom was favored due to its more interactive features, although Google Meet remained a simple and accessible option. In conclusion, Zoom is more effective in increasing student engagement, making it a recommended platform for online learning.